Decreased Recombination Through the Use of a Non‐Fullerene Acceptor in a 6.4% Efficient Organic Planar Heterojunction Solar Cell. Issue 8 (29th January 2014) - Verreet, Bregt; Cnops, Kjell; Cheyns, David; Heremans, Paul; Stesmans, Andre; Zango, German; Claessens, Christian G.; Torres, Tomas; Rand, Barry P.
<x xml:space="preserve">Abstract</x> An optimization of several aspects of planar heterojunction solar cells based on boron subnaphthalocyanine chloride (SubNc) as a donor material is presented. The use of hexachlorinated boron subphthalocyanine chloride (Cl6SubPc) as an alternative acceptor to C60 allows for the simultaneous increase of the short‐circuit current, fill factor, and open‐circuit voltage compared to cells with fullerene acceptors. This is due to the complementary absorption of Cl6SubPc versus SubNc, reduced recombination at the heterointerface, and improved energetic alignment. Furthermore, insertion of a thin diindeno[1, 2, 3‐cd:1′, 2′, 3′‐lm]perylene (DIP) layer at the anode results in a very significant 60% increase in photocurrent owing to reduced exciton quenching at the anode. The simultaneous improvement of all three solar cell parameters results in a power conversion efficiency of 6.4% for a non‐fullerene planar heterojunction cell.